2011
DOI: 10.1002/bsl.922
|View full text |Cite
|
Sign up to set email alerts
|

Stalkers and harassers of British Royalty: an exploration of proxy behaviours for violence

Abstract: Study of risk factors for violence to prominent people is difficult because of low base rates. This study of harassers of the royal family examined factors suggested in the literature as proxies for violence--breaching security barriers, achieving proximity, approach with a weapon, and approach with homicidal ideation. A stratified sample of different types of approach behaviour was randomly extracted from 2,332 Royalty Protection Police files, which had been divided into behavioural types. The final sample si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 22 publications
0
20
1
1
Order By: Relevance
“…This evidence is a clear indication that if sample sizes allow, severe violence should be examined separately in studies that focus on sex differences in stalking. Contrary to Thompson et al's (2012) results, severe violence has been shown to have its own correlates in the stalker violence prediction literature and would appear to be more frequently perpetrated by males (e.g., James & Farnham, 2003;Rosenfeld & Lewis, 2005).…”
Section: Opposite Sex Stalkingcontrasting
confidence: 61%
“…This evidence is a clear indication that if sample sizes allow, severe violence should be examined separately in studies that focus on sex differences in stalking. Contrary to Thompson et al's (2012) results, severe violence has been shown to have its own correlates in the stalker violence prediction literature and would appear to be more frequently perpetrated by males (e.g., James & Farnham, 2003;Rosenfeld & Lewis, 2005).…”
Section: Opposite Sex Stalkingcontrasting
confidence: 61%
“…As the nascent discipline of threat assessment matures, it is pertinent to revisit and refine terminology to standardize both practice and further research. One such concept is that of “warning behaviors” (James et al, ), variously termed by others as “signaling the attack” (Vossekuil, Reddy, Fein, Borum, & Modzeleski ), “tell‐tale behaviors” or “high risk indicators” (Calhoun & Weston, ), “stalking‐type behavior” (Mullen et al, ) and “pre‐attack signals” (Dietz & Martell, ). These concepts in turn are also closely linked to those of “leakage” (Meloy & O'Toole, 2011; O'Toole, ) and behaviors on a “pathway to violence” (Calhoun & Weston, 2003; Fein et al, ).…”
mentioning
confidence: 99%
“…There is a growing consensus that PMCOs frequently engage in behaviors that, if noticed and reported, can serve as warnings and aid in the identification of those on a trajectory toward attack. The existence of such “warning behaviors” was proposed by the Fixated Research Group in a series of studies primarily regarding approaches and communications to the British Royal Family (James et al., , , ; Meloy, Hoffmann, Guldimann, & James, ; Mullen et al., ). Relying on slightly different conceptualizations, these patterns of behavior indicating an increasing threat have also been described as “signaling the attack” (Vossekuil et al., ), “high‐risk indicators” (Calhoun & Weston, ), and “red flag indicators” (White, Meloy, Mohandie, & Kienlen, ).…”
Section: Threat Assessmentmentioning
confidence: 99%